Malignant Progression Contributes to the Failure of Combination Therapy for Atypical Meningiomas - Zhang, Qing; Wen, Zheng; Ni, Ming; Li, Da; Wang, Ke; Jia, Gui-Jun; Wu, Zhen; Zhang, Li-Wei; Jia, Wang; Wang, Liang; Zhang, Jun-Ting (Frontiers in Oncology, 2021)
Objective To investigate the independent risk factors for recurrence in intracranial atypical meningiomas (AMs) treated with gross total resection (GTR) and early external beam radiotherapy (EBRT). Methods Clinical, radiological, and pathological data of intracranial AMs treated with GTR-plus-early-EBRT between January 2008 and July 2016 were reviewed. Immunohistochemical staining for Ki-67 was performed. Kaplan–Meier curves and univariate and multivariate Cox proportional hazards regression analyses were used to explore independent predictors of tumor recurrence. Chi square test was performed to compare viariables between subgroups. Results Forty-six patients with intracranial AMs underwent GTR and early EBRT. Ten (21.7%) recurred and three (6.5%) died during a median follow-up of 76.00 months. Univariate and multivariate Cox analyses revealed that malignant progression (MP) (P = 0.009) was the only independent predictor for recurrence, while Ki-67 was of minor value in this aspect (P = 0.362). MP-AMs had a significantly higher recurrence rate (P = 0.008), a higher proportion of irregularly shaped tumors (P = 0.013) and significantly lower preoperative Karnofsky Performance Scale (KPS) scores (P = 0.040) than primary (Pri) AMs. No significant difference in Ki-67 expression was detected between these subgroups (P = 0.713). Conclusions MP was significantly correlated with an increased incidence of recurrence in GTR-plus-early-EBRT-treated intracranial AMs. Significantly higher frequencies of tumor relapse and irregularly shaped tumors and lower preoperative KPS scores were observed in MP-AMs compared with Pri-AMs. Ki-67 expression is of minor value in predicting tumor recurrence or distinguishing tumor origins in AMs.